2010
DOI: 10.1523/jneurosci.1314-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Setdb1 Histone Methyltransferase Regulates Mood-Related Behaviors and Expression of the NMDA Receptor Subunit NR2B

Abstract: Histone methyltransferases specific for the histone H3-lysine 9 residue, including Setdb1 (Set domain, bifurcated 1)/Eset/Kmt1e are associated with repressive chromatin remodeling and expressed in adult brain, but potential effects on neuronal function and behavior remain unexplored. Here, we report that transgenic mice with increased Setdb1 expression in adult forebrain neurons show antidepressant-like phenotypes in behavioral paradigms for anhedonia, despair, and learned helplessness. Chromatin immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 91 publications
4
94
0
Order By: Relevance
“…Acute and subchronic (7 day) stress increased global levels of H3K9me3 in the DG and CA1 regions, whereas chronic (21 days) stress decreased the same mark in these regions, and the latter effect was reversed by antidepressant treatment. H3K9me3 is typically thought to be involved in heterochromatin formation and maintenance, but has recently been shown to be regulated by several types of chronic stimuli; for example, cocaine treatment (Maze et al, 2011), as well as being involved in regulating transcription of a very small subset of genes (Jiang et al, 2010). study suggests that H3K9me3 may have an adaptive role in stress models, a possibility supported by the antidepressant effects of overexpressing SETDB1 (a KMT that catalyzes H3K9me3) in broad forebrain regions (Jiang et al, 2010).…”
Section: Histone Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute and subchronic (7 day) stress increased global levels of H3K9me3 in the DG and CA1 regions, whereas chronic (21 days) stress decreased the same mark in these regions, and the latter effect was reversed by antidepressant treatment. H3K9me3 is typically thought to be involved in heterochromatin formation and maintenance, but has recently been shown to be regulated by several types of chronic stimuli; for example, cocaine treatment (Maze et al, 2011), as well as being involved in regulating transcription of a very small subset of genes (Jiang et al, 2010). study suggests that H3K9me3 may have an adaptive role in stress models, a possibility supported by the antidepressant effects of overexpressing SETDB1 (a KMT that catalyzes H3K9me3) in broad forebrain regions (Jiang et al, 2010).…”
Section: Histone Methylationmentioning
confidence: 99%
“…H3K9me3 is typically thought to be involved in heterochromatin formation and maintenance, but has recently been shown to be regulated by several types of chronic stimuli; for example, cocaine treatment (Maze et al, 2011), as well as being involved in regulating transcription of a very small subset of genes (Jiang et al, 2010). study suggests that H3K9me3 may have an adaptive role in stress models, a possibility supported by the antidepressant effects of overexpressing SETDB1 (a KMT that catalyzes H3K9me3) in broad forebrain regions (Jiang et al, 2010). Further work is needed to understand the underlying mechanisms involved, in particular, whether these adaptive effects of H3K9me3 are mediated by the repression of specific genes or, rather, of intergenic elements.…”
Section: Histone Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ESET is expressed in ES cells and the postnatal brain (Ryu et al, 2006;Matsui et al, 2010;Jiang et al, 2010), but expression in the developing brain has not been examined extensively. We therefore performed in situ hybridization and immunohistochemical analyses with mouse embryos at different developmental stages.…”
Section: Eset Is Expressed By Npcs In the Developing Brainmentioning
confidence: 99%
“…Despite of the growing realization of the importance of these and other higher order chromatin structures for transcriptional regulation, very little is known about their role in the nervous system. Until recently, there were only three studies in the literature that explored loop formations in brain tissue (Dhar et al, 2009;Horike et al, 2005;Jiang et al, 2010), with a few additional papers using the brain as negative control for their studies on the sensory epithelium of the nose (Lomvardas et al, 2006) or the hematopoetic system (Simonis et al, 2006). However, to date, nothing is known about chromatin loopings in human brain.…”
Section: Epigenome Organization and Higher Order Chromatin Structuresmentioning
confidence: 99%